PERANCANGAN GAME “TALES OF SARIP TAMBAK OSO” BERBASIS DESKTOP MENGGUNAKAN UNITY - Alvito Dian Pratama Putra; Cindy Taurusta; Irwan Alnarus Kautsar (Politeknik Bisnis Indonesia, 2024)
Folklore is a story from the past that has been passed down from generation to generation in a society that serves as a medium to convey the values contained in the life believed by the community. One of the folktales originating from Sidoarjo that contains character education values in the development of the storyline is